Clinical and Histopathologic Features Can Help Target Immunohistochemical Stain Use in the Diagnosis of Viral Esophagitis. Issue 10 (November 2021) - Desai, Nirali; Albahra, Said; Lucas, Elena; Singal, Amit G.; Hammer, Suntrea T.G.; Gopal, Purva
Abstract : Objectives: Herpes simplex virus (HSV) and cytomegalovirus (CMV) immunohistochemical stains (IHC) are frequently applied on esophageal biopsies. Our aims were to identify IHC use patterns in viral esophagitis (VE), and clinicopathologic features of VE that could guide IHC use. Methods: We included 58 VE cases and 60 controls, defined as patients with negative HSV/CMV IHC between January 2006 and July 2017. Biopsies were reviewed and histologic features and clinical data recorded. Results: Thirteen cases required IHC for diagnosis. IHC was performed in 13 HSV and 5 CMV cases where diagnostic viral inclusions were present. VE patients were more likely to have endoscopic ulcer ( P =0.002) and be immunocompromised ( P <0.001). Pretest clinical concern for VE was common ( P =0.006). Histologically, VE patients were more likely to have ulcer ( P =0.004), ulcer exudate rich in neutrophils and histiocytes ( P =0.001), neutrophils in squamous mucosa ( P <0.001), histiocyte aggregates >15 ( P <0.001) and spongiosis ( P <0.001). Controls had frequent eosinophils, alone ( P =0.008) or admixed with other inflammatory cells ( P <0.0001). Conclusions: IHC is used in VE biopsies despite definite viral inclusions on hematoxylin and eosin and in patients without concerning histology or clinical concern for VE. History, endoscopic findings, and histology can be used to better target IHC use in VE.